Optimization of Parameters for Pedestrian Simulation Software: A Case Study of Emergency Evacuation Experiments - Gaddam, Hari Krishna; Devi Vanumu, Lakshmi; Arya, Aditya; Ramachandra Rao, K. (Communications - Scientific Letters of the University of Zilina, 2022)
This research study provides a new framework to optimize pedestrian simulation parameters required to replicate emergency evacuation conditions specifically observed in high rise buildings, passenger vehicles and transport terminals. The simulation experiments are performed with generalised social force model in VISWALK simulation environment. The data required for optimization are obtained by conducting several evacuation experiments. The results indicate that pedestrian behavioural aspects, such as the relaxation time, distance from the other pedestrian and force exerted by closest pedestrians, have a significant impact on total evacuation time. The outcomes are in consistence with field observations and the calibrated parameters would help in simulating future scenarios including building level simulations and further simulating emergency evacuation of passengers from transport terminals and vehicles.
Keywords: social force model; VISWALK; pedestrian simulation; classroom evacuation; sensitivity analysis; calibration; validation